Analisis Absorptive Capacity Terhadap Sustainable Business - Rahadian, Rahadian; Siwiyanti, Leonita (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important economic sector in Indonesia that contributes significantly to GDP and job creation, but face challenges in implementing sustainable business practices, especially related to limited access to technology, leadership style, and digital marketing. This study aims to analyze the effect of entrepreneurial leadership and digital marketing on sustainable business, with absorptive capacity as a mediating variable. Using a quantitative approach, this study tested the hypothesis on 133 traditional food MSMEs in Sukabumi City selected through purposive sampling, with data analysis using Structural Equation Modeling (SEM) via SPSS AMOS. The results showed that entrepreneurial leadership and digital marketing positively and significantly influenced absorptive capacity. In addition, entrepreneurial leadership also had a positive and significant effect on sustainable business. Although digital marketing did not have a significant direct effect on sustainable business, absorptive capacity was shown to have a positive and significant effect on sustainable business. These findings indicate that entrepreneurial leadership and digital marketing increase the adaptability of MSMEs by increasing the capacity to absorb external information, which in turn supports adaptive strategies and business sustainability. Overall, entrepreneurial leadership and absorptive capacity are the main drivers of MSME business sustainability, emphasizing the importance of mastering digital technology and entrepreneurial leadership strategies to achieve sustainability.